2011
DOI: 10.1063/1.3670879
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the electrical transport properties of double-walled carbon nanotubes by semiconductor and semi-metal filling

Abstract: Manipulating the electrical properties of carbon nanotubes through semi-metal or semiconductor filling is of paramount importance in the realization of nano-electronic devices based on one dimensional composite materials. From low temperature electrical conductivity measurements of a network, of empty and filled double-walled carbon nanotubes (DWNT’s), we report a transition in electrical transport features from hopping to weakly activated conduction by HgTe filling and also semi-metallic conduction in seleniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…After 250°C, the conductance decreases irreversibly due to structural modification . The reversible increase in the conductivity (≤250°C) is explained by the semiconductor nature of the sample, whereas the decrease in the conductance can be explained by the transformation from semiconductor to metallic behavior . The reversible trend under dry air and humid air up to 250°C is verified for our CF/CNT/SiOCN sensor.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…After 250°C, the conductance decreases irreversibly due to structural modification . The reversible increase in the conductivity (≤250°C) is explained by the semiconductor nature of the sample, whereas the decrease in the conductance can be explained by the transformation from semiconductor to metallic behavior . The reversible trend under dry air and humid air up to 250°C is verified for our CF/CNT/SiOCN sensor.…”
Section: Resultssupporting
confidence: 64%
“…The activation energy of CF/CNT/SiOCN is calculated as low as 1 meV for the 1st step and other cooling steps (<440°C). This kind of extremely small band gap is reported in literature for semimetallic CNTs whose diameter is slightly greater than 1 nm . This is considered as an indication of the formation of thin layer of SiOCN on CNTs.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…3 Earlier experimental and theoretical works on filled DWNTs have shown that these nanotubes demonstrate unique1D features due to the nearly structurally perfect inner wall that is protected by the outer wall. 6,7 The inner wall thus remains unaffected by the chemical purification processes, and substrate interference effects although the outer wall of DWNTs can be biased in such a manner it behaves as a gate. 8 However, the alignment of the tubes is necessary to observe 1D transport which can be affected by the interaction of tubes in a bundle of CNTs.…”
mentioning
confidence: 99%
“…Their cylindrical shape and chemical structure (honeycomb carbon lattice) confer the material unique properties with potential applications in biomedicine [1,2], catalysis [3], nanocomposites [4] or electronics [5]. Their range of application can be further expanded by the formation of hybrid materials via endohedral filling [6][7][8][9] or external decoration [10,11]. The encapsulation at the nanoscale, which is the focus of the present review, allows tuning the properties of both the guest species that can undergo modifications of their space configuration, crystalline structure or the atomic ratio of their constituting elements [7] and the host, which electronic and optical properties can also be impacted due to the interaction between the new encapsulated material and the walls of the nanotubes [8,9].…”
Section: Introductionmentioning
confidence: 99%